2021
DOI: 10.3390/pathogens10091113
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carcinoma: The Role of the EGFR in Epstein–Barr Virus Infection

Abstract: Epstein–Barr virus (EBV), a type 4 γ herpes virus, is recognized as a causative agent in nasopharyngeal carcinoma (NPC). Incidence of EBV-positive NPC have grown in recent decades along with worse outcomes compared with their EBV-negative counterparts. Latent membrane protein 1 (LMP1), encoded by EBV, induces NPC progression. The epidermal growth factor receptor (EGFR), a member of the ErbB family of receptor tyrosine kinases (RTK), is a driver of tumorigenesis, including for NPC. Little data exist on the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 118 publications
0
10
0
2
Order By: Relevance
“…EBV infection is common worldwide and is associated with infectious mononucleosis, Burkitt's lymphoma, classical Hodgkin's lymphoma, gastric cancers and NPC ( 26 ). Almost 98% of NPC cases are closely related to EBV infection ( 27 ), which may promote the progression of NPC ( 28 ). A large number of studies have indicated that the level of free EBV DNA in the plasma of patients with NPC is highly correlated with its prognosis and is widely used as a clinical marker in the clinical diagnosis and monitoring of NPC ( 1 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBV infection is common worldwide and is associated with infectious mononucleosis, Burkitt's lymphoma, classical Hodgkin's lymphoma, gastric cancers and NPC ( 26 ). Almost 98% of NPC cases are closely related to EBV infection ( 27 ), which may promote the progression of NPC ( 28 ). A large number of studies have indicated that the level of free EBV DNA in the plasma of patients with NPC is highly correlated with its prognosis and is widely used as a clinical marker in the clinical diagnosis and monitoring of NPC ( 1 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the present findings, it has been reported that EGFR overexpression is a potential prognostic biomarker for advanced-stage patients with a poor outcome and is relatively common in NPC ( 32 ). Furthermore, EGFR is highly expressed in EBV-infected cells and may promote the neoplastic transformation of EBV-positive cells; importantly, EGFR may be necessary for the internalization and fusion of EBV in NPC cells ( 28 ). However, only a small amount of information regarding EGFR expression is available ( 5 22 ), despite non-small cell cancers, including large-cell cancers, being associated with EBV infection ( 6 , 10 , 13 , 15 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The virus mimics latency models seen in certain malignant tumors linked to EBV and utilizes them for various viral life cycle stages [ 11 ]. EBV must also multiply periodically during its life cycle to generate infectious virus for transmission to a new sensitive host, with epithelial regions in the oropharynx and salivary glands showing the main viral replication sites [ 108 ]. Thus, the natural history of chronic EBV infection is comparable to that of another herpesviruses.…”
Section: Primary Gene Product (Genetic Variability)mentioning
confidence: 99%
“…Despite the fact that around half of individuals living in China or moving to Southeast Asia have NPCs, the recurrence is significantly higher among Chinese born in Western nations than Caucasians [ 77 ]. Likewise, contrasted with French men born in the south of France, French men born in North Africa had a higher risk of NPC [ 108 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The onset is concealed, and the main pathological types of most cancers are medium and low-differentiated squamous cell carcinoma. Clinically, radiotherapy combined with chemotherapy has achieved favorable results in early-stage patients, but a considerable number of patients still experience metastasis and recurrence, thus affecting their prognosis ( Peng et al, 2021 ). Therefore, other prevention and treatment strategies need to be developed in the clinic.…”
Section: Introductionmentioning
confidence: 99%